Back-to-front Down-Under? Estimating the Part-Time / Full-Time Wage Differential over the Period 2001-2003 - Booth, A; Wood, M (My University, 2006)
In 2003, part-time employment in Australia accounted for over 42% of the Australian female workforce, nearly 17% of the male workforce, and represented 28% of total employment. Of the OECD countries, only the Netherlands has a higher proportion of working women employed part-time and Australia tops the OECD league in terms of its proportion of working men who are part-time. In this paper we investigate part-time full-time hourly wage gaps using important new panel data from the first four waves of the new Household, Income and Labour Dynamics in Australia Survey. We find that, once unobserved individual heterogeneity has been taken into account, part-time men and women typically earn an hourly pay premium. This premium varies with casual employment status, but is always positive, a result that survives our robustness checks. We advance some hypotheses as to why there is a part-time pay advantage in Australia.
Centre for Economic Policy Research, the Australian National University, Discussion Paper
Keywords: Gender; Employment -- Hours; Finance -- Income (Salary and Wages); Employment; Finance; Income, wealth and finances; Labour market; Income, wealth and finances; Employment and unemployment